Pooled efficacy and safety of eslicarbazepine acetate as add‐on treatment in patients with focal‐onset seizures: Data from four double‐blind placebo‐controlled pivotal phase III clinical studies. (13th October 2017) - Elger, Christian; Koepp, Mathias; Trinka, Eugen; Villanueva, Vicente; Chaves, João; Ben‐Menachen, Elinor; Kowacs, Pedro A.; Gil‐Nagel, António; Moreira, Joana; Gama, Helena; Rocha, José‐Francisco; Soares‐da‐Silva, Patrício
Summary: Purpose: Pooled evaluation of the key efficacy and safety profile of eslicarbazepine acetate (ESL) added‐on to stable antiepileptic therapy in adults with focal‐onset seizures. Methods: Data from 1703 patients enrolled in four phase III double‐blind, randomized, placebo‐controlled studies were pooled and analyzed. Following a 2 week titration period, ESL was administered at 400 mg, 800 mg, and 1200 mg once‐daily doses for 12 weeks (maintenance period). Pooled efficacy variable was standardized (/4 weeks) seizure frequency (SSF) analyzed over the maintenance period as reduction in absolute and relative SSF and proportion of responders (≥50% reduction in SSF). Pooled safety was analyzed by means of adverse events and clinical laboratory assessments. Results: SSF was significantly reduced with ESL 800 mg ( P  < 0.0001) and 1200 mg ( P  < 0.0001) compared to placebo. Median relative reduction in SSF was 33.4% for ESL 800 mg and 37.8% for 1200 mg (placebo: 17.6%), and responder rate was 33.8% and 43.1% (placebo: 22.2%). ESL was more efficacious than placebo regardless of gender, geographical region, epilepsy duration, age at time of diagnosis, seizure type, and type of concomitant antiepileptic drugs (AED). Incidence of adverse events (AEs) and AEs leading to discontinuation was dose dependent. Most common AEs (>10% patients) were dizziness, somnolence, and nausea. The incidence of treatment‐emergent AEs (dizziness, somnolence, ataxia, vomiting, and nausea) was lower in patients who began taking ESL 400 mg (followed by 400 mg increments to 800 or 1200 mg) than in those who began taking ESL 600 mg or 800 mg. Conclusions: Once‐daily ESL 800 mg and 1200 mg showed consistent results across all efficacy and safety endpoints, independent of study population characteristics and type of concomitant AEDs. Treatment initiated with ESL 400 mg followed by 400 mg increments to 800 or 1200 mg provides optimal balance of efficacy and tolerability.